Rate of Occurrence of Fatal Accidents in Malaysian Construction Industry after BIM Implementation - Aminu Darda’u Rafindadi; Aminu Darda’u Rafindadi; Madzlan Napiah; Idris Othman; Miljan Mikić; Yasser Yahya Al-Ashmori (International Journal of Engineering and Management Research, 2020)
Construction industry impacts the health and safety of its workers tremendously. This study is aimed to determine the rate of occurrence of fatal accidents after BIM implementation in Malaysia. The data used for the research was obtained from the Department of Safety and Health (DOSH) website, and it was validated by the relevant professionals through interview. This descriptive analysis was grounded in 796 fatal accidents over the period of 2010-2018. Of those accidents, 38.16% were related to fall-related, 30.39% struck-by, 17.67% caught in-between, 9.89% drowning/asphyxiation and 3.89% others. The results indicate that the types of accidents identified are similar to that of most countries in the world. The findings also revealed that the accidents had occurred because one or combination of the following: management's failure, unsafe site conditions, workers behavior, and environmental factors. Future work will concentrate on the use of BIM-based tools for job hazard identification and safety training.